Hospital Management System Design and Implementational - Saif Ghazi Mohammed Alsamarrai; Asst. Prof. Dr. Sefer Kurnaz (Scientific Trends, 2023)
We anticipate that technology is going to keep to have a significant impact on the healthcare industry and hospitals. For this reason, we worked on this project to promote hospital systems generally and do away with the paper system. We constantly see researchers and programmers working in the area of in-formation technology growing and improving this harmonious relationship between health and technol-ogy. We began developing web apps. And some languages to assist us and grant us flexibility in design, like PHP with the aid of Java script and a straightforward addition of and a potent database of a language to complete an effective and integrated system with many features and advantages to eradicate many issues that exist in paper systems as the issue of time, data volume, the speed and quality of work, and many more. We finished a powerful hospital management system that is free from issues and faults, is characterized by dependability, high performance, and is prepared for the future, among other issues that we tried to tackle in the end.
Keywords: Admin, CSS, Dashboard, Employees, Patient, MYSQL, Web-Based Application.